The township: Their economics situation - Margin Manautou, Emilio (UNIVERSIDAD DE SONORA, 2019)
This document refers to the differents incomes that the municipalities in Mexico can get, the problem faced the more poor in order to meet their annual budgets, their possible causes and tips to achieve a better distribution of resources generated from the less important municipalities but that favor economically the capital of the State or to others who have own wealth , and with this avoid the impact of the reduction of the federal public expenditure announced by the SHCP for 2017, in similars terms at 2016.